Diversity of dialects of the novel characters according to the descriptive stylistics, the novel (Alye di ye pre) as an example (Raparin Journal of Humanities (RJH), 2024)
Methods of style directions are considered as backgrounds for certain reasons and mechanisms of the methods followed, to interpret linguistic or literary discourses and to identify certain methodological characteristics according to certain scientific methods to avoid inferential decisions and interpretations, according to linguistic levels, As a result of contemporary linguistic research done through the use of linguistic sciences in order to identify aesthetic aspects of literary works and writings.      Descriptive stylistics is considered an important direction for interpretation of any innovative discourse, because the nature of methodological research, some linguistic directions are important for interpretation of any text it takes hold of itself. Because the concept of expression among linguists is connected the material form of speech, such as speech versus content, which becomes a linguistic meaning for that speech, or the sounds spoken and written on the surface of expression with surface of content, because language is speech. Either they are just some voices and each nation speaks through them, or they are voices that express their actions.     This research is entitled (Diversity of dialects of the novel characters according to the descriptive stylistics, the novel (Alye di ye pre) as an example), is an attempt to explain the language expression of characters according to the theory of descriptive stylistics.     Expression methodology is a good basis for interpreting text according to the mechanisms it works with in order to convey the right direction for understanding the message of each text.